A Study on Nutritional Status of HIV Positive Children and Its Correlates in a Tertiary Health Care Institution of Kolkata - Sukesh Das; Bikas C Muhuri; Aparajita Dasgupta (Medsci Publications, 2017)
Background: Nutritional status is vital to survival and wellbeing of children especially if they are HIV infected. In this context this study was attempted to assess nutritional status of HIV infected children of 0-14 yrs old.Also it aimed at finding out association,if any,between nutritional status of the children with socio-demographic and other factors. Methodology: This cross-sectional study was conducted at Regional Pediatric ART centre, Medical College and Hospital, Kolka-ta. 202 HIV positive children of the above centre were study participants.Study duration was one year. Relevant information was collected by interviewing caregivers and taking anthropometric mea-surements. Results: Among underfive children, underweight, wasted and stunted were 31.7%, 26.9% and 19.5% respectively. Among all the children 29.2% were thin and 10.4% were severely thin whereas 55% were stunted and 24.8% were severely stunted.There were differences among boys and girls regarding nutritional status, which were not statistically significant.The thinness of the children was positively associated with older age-groups (i.e. =>5 yrs), decrease of CD4% and the status of not taking ART whereas stunting was positively associated with older age-groups (ie =>5 yrs). Conclusion: The findings of this study may be useful for similar settings and for policymakers for planning interventions.